New born hearing screening programme at tertiary care hospital from South Karnataka-our experience - Dr. V.G. Manjunath; Dr. Shravan Krishna Reddy; Dr. K. Jagadish Kumar (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Universal hearing screening is implemented in many developed countries. However, neither universal screening, nor high risk screening, exists uniformly all over India. Screening of only high risk neonates can miss upto 50% of babies with hearing loss, hence a cost effective universal screening programme will be the viable option. Objective: To determine the incidence of hearing impairment in normal newborns with no risk factors delivered in a tertiary hospital in south Karnataka, India. Methods: All eligible newborns were screened using two staged Transient Evoked Oto Acoustic Emissions (TEOAE) at birth and at 4-6 weeks of age and confirmatory test by auditory brainstem response (ABR) at 3 months of life. Results: Out of 977 babies, 14 were detected with hearing loss at first follow up at 4-6 weeks of age. Of these 14 babies,6 were confirmed to have hearing impairment using ABR at 3 months of age. Two of them had severe sensory neural hearing loss and the other four were diagnosed with moderate to severe hearing loss. The incidence of hearing loss in our study is 6.1 per 1000 neonates with no risk. Conclusions: A two-staged TEOAE hearing screening can be feasible option as newborn hearing screening method, for early detection of hearing impairment in all major hospitals. Universal hearing screening is the need of the hour to detect large number of hearing impaired in the magnanimous “no risk” newborn population in our country.